Enhancement of tumor radio-response by vinorelbine in vitro and vivo in mice lung tumor xenografts - Gao, Chunling; Cheng, Xiaofeng; Wang, Xiaoliang; Zhang, Beibei; Zhang, Jiao (European Journal of Oncology and Environmental Health, 2015)
Objective: The aim of the experiment was to explore the optimal radioenhancement effect of vinorelbine on human lung adenocarcinoma. Methods: After combination treatment of 0.1 or 1nM vinorelbine with or without irradiation, cell viability was determined using clonogenic assays. Genotoxic potential of vinorelbine (NVB) and radiation (RT) alone, as well as in interaction, was determined in 973 cells using the alkaline comet assay. A male nude mouse lung tumor xenograft model was established by injecting 973 cells into nude mice. The nude mice were randomly divided into six groups: control group, 10Gy group, 20Gy group, vinorelbine group, vinorelbine + 10Gy group, vinorelbine + 20Gy group (n=8 mice per group). Vinorelbine was injected at 2 mg/kg. Tumors were measured every other day using vernier calipers. The tumor volume and growth delay were calculated. Enhancement factor (EF) was used to evaluate the radiation enhancement. Results: Vinorelbine had a signiﬁcant effect on clonogenic survival in response to radiation in 973 cell lines at the higher dose of 1nM. The combination of vinorelbine and radiation caused a signiﬁcant increase in tail moment compared to vinorelbine and radiation alone. Tumor growth inhibition in the vinorelbine + RT group was higher than in the radiation group or vinorelbine group (p < 0.05). The values of EF were 1.1 and 1.2, respectively. The longest time of tumor growth delay was 28 days in the vinorelbine + 20Gy group. Conclusions: Vinorelbine possesses radioenhancing properties for lung adenocarcinoma.